2012
DOI: 10.4274/tpa.634
|View full text |Cite
|
Sign up to set email alerts
|

Lennox-Gastaut sendromlu hastaların klinik özellikleri ve uzun süreli seyri

Abstract: Aim:The aim of this study was to retrospectively evaluate clinical features, treatment and prognosis of 20 patients followed up as Lennox-Gastaut Syndrome in ESOGU in the Division of Pediatric Neurology. Material and Method: Multiple different types of seizure, diffuse spike-wave pattern(<3 Hz) on electroencephalogram, psychomotor retardation were the diagnostic criteria for Lennox-Gastaut Syndrome. The patients who had no etiologic reason were described as the idiopathic type. Prenatal, natal and postnatal ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 23 publications
1
19
0
2
Order By: Relevance
“…Seizure frequency ranged widely within and across studies, which may be partly owing to interindividual heterogeneity; in one study, baseline seizure frequency was 15–3000 seizures per month 46,51 . These findings aligned with those from studies in which individuals were categorized by seizure frequency; 50%–100% of individuals were reported to have daily seizures, and those without daily seizures were usually reported to have seizures at least once per week 18,20,23,26,28,34–36,52–58 …”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Seizure frequency ranged widely within and across studies, which may be partly owing to interindividual heterogeneity; in one study, baseline seizure frequency was 15–3000 seizures per month 46,51 . These findings aligned with those from studies in which individuals were categorized by seizure frequency; 50%–100% of individuals were reported to have daily seizures, and those without daily seizures were usually reported to have seizures at least once per week 18,20,23,26,28,34–36,52–58 …”
Section: Resultssupporting
confidence: 61%
“…28,[37][38][39][40] These data were generally aligned with those from studies that reported the proportion of individuals experiencing different numbers of seizure types (Figure 3). 20,21,[26][27][28][29][30][31][32][33][34][35][36] One study reported a high prevalence of individuals with one seizure type (38%); however, this study used historical records of seizure types experienced over 14 years. 29 Four studies reported a decrease in the number of seizure types experienced per individual during the study, which may reflect changes with age.…”
Section: Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…İdiyopatik LGS olgularında seyir daha iyidir. [14] Lennox-Gastaut sendromu etiyolojisinde saptanan olgularda bant ne kadar kalın ise prognozun o kadar ağır olduğu bilinmektedir. [4] Hastamızda kraniyal MRG'de bant heterotopi ile uyumlu olarak korteks ile ventrikül arasında iyi sınırlı gri madde ile izointens sinyal değişikliği izlendi.…”
Section: Discussionunclassified
“…Erken çocukluk döneminde başlayan birden fazla değişik tip nöbet, bilişsel işlevlerde bozulma ve EEG de yaygın yavaş diken-dalga (1-3 Hz/sn) izlenir. [14] Bizim hastamızın EEG'sinde 2-2.5 hz diken dalga, multipl diken ve hızlı ritmler görüldü.…”
Section: Discussionunclassified